A better investment climate for everyone (Washington, D.C. World Bank ; New York Oxford University Press, 2004)
"Firms and entrepreneurs of all types-from micro-enterprises to multinationals-play a central role in growth and poverty reduction. Their investment decisions drive job creation, the availability and affordability of goods and services for consumers, and the tax revenues governments can draw on to fund health, education, and other services. Their contribution depends largely on the way governments shape the investment climate in each location-through the protection of property rights, regulation and taxation, strategies for providing infrastructure, interventions in finance and labor markets, and broader governance features such as corruption. The World Development Report 2005 argues that improving the investment climates of their societies should be a top priority for governments."--World Bank summary.
pt. 1. Improving the investment climate -- The investment climate, growth, and poverty -- Confronting the underlying challenges -- Tackling a broad agenda -- pt. 2. Delivering the basics -- Stability and security -- Regulation and taxation -- F inance and infrastructure -- Workers and labor markets -- pt. 3. Going beyond the basics? -- Selective interventions -- International rules and standards -- pt. 4. How the international community can help -- How the international community can help -- Selected indicators -- Measuring the investment climate -- Selected world development indicators.
"This Report has been prepared by a team led by Warrick Smith ..."--P. xv.
Includes bibliographical references (p. 210-242).
"This Report has been prepared by a team led by Warrick Smith ..."--P. xv.
Also available on the World Wide Web.
Keywords: World Bank; Business enterprises; Commercial policy; Costs, Industrial; Economic policy; Investments; Desenvolvimento econ?omico.; Investeringen; Ondernemingsklimaat; Ontwikkelingseconomie; Desenvolvimento SustentâAvel.